INVESTORS’ VALUATION OF CORPORATE CO2 EMISSIONS: THE IMPACT OF THE COVID-19 CRISIS - FROMONT, Emmanuelle; Le Hoa VO, Le Hoa VO; LUX, Gulliver (Bankers, Markets & Investors, 2023)
This study examines the impact of the COVID-19 crisis on the valuation of CO2 emissions by investors. Using the sample constituted by large French companies (SBF 120) having published their carbon emissions from 2016 to 2021, we show that investors are sensitive to firms’ carbon emissions and value them negatively over the period regardless the environmental sensitivity of the firm’s activity sector. We also demonstrate that under the pressure of the COVID-19 crisis, investors penalize more heavily high polluting firms while their valuation of low polluting firms does not seem to be impacted by the crisis. Therefore, our findings suggest that it is important for firms, especially high-emitting firms, to continue to reduce their carbon emissions in order to earn andmaintain investors’ confidence after the crisis. Our managerial contribution emphasizes the confirmation that the COVID-19 shock could be a good opportunity for both firm and investor to pursue their clean technologies development and investment to deal with climate change.